McDxNewJeans collaborative campaign: How Co-Branding impacts fandom purchase behavior - Thoyib Amali, Muhammad; Camelia Putri, Lathifa (Universitas Ahmad Dahlan, 2024)
The effective marketing approach that has gained popularity in recent decades as an innovative strategy to enhancing consumer engagement and boost visibility is co-branding, where two or more brands collaborate to create unique products or marketing campaigns that combine their strengths and appeal. This study aims to examine the influence of co-branding between McDonald's and NewJeans on fandom purchase behavior, particularly focusing on how brand image and co-branding shape consumer attitudes and behavior. Using an explanatory quantitative approach, 120 members of the NewJeans fandom in Indonesia were surveyed. Data were analyzed using Smart PLS, and mediation effects were tested with the Sobel test. The findings reveal a significant impact of both McDonald's and NewJeans brand image on co-branding campaign, which in turn positively influences fandom attitudes toward McDonald’s K-Meals and drives purchase behavior. Additionally, Co-branding fully mediates the relationship between McDonald’s brand image and fandom attitudes, while it partially mediates the relationship between NewJeans’s brand image and fandom attitudes. Moreover, attitudes towards K-Meals serve as a partial mediator between the co-branding campaign and purchase behavior. Overall, this study highlights the significance of strategic co-branding campaigns as a collaborative marketing approach to strengthen consumer engagement, especially within K-pop fandom communities.